Optimalisasi Penggunaan Alat Perlindungan Diri (APD) pada Masyarakat dalam Rangka Mencegah Penularan Virus COVID-19 - Ni Made Nopita Wati; Ni Kadek Yuni Lestari; Desak Made Ari Dwi Jayanti; Nyoman Sudarma (Poltekkes Kemenkes Surakarta, 2020)
Background: COVID-19 is a pandemic that is being faced by all people in the world. COVID-19 transmission can be prevented by optimizing the use of PPE (Personal Proctection Equipment) such as masks. But there are still many people who do not know, understand and have the awareness to use them. Purpose of this study is to optimize using personal proctection equipment in community. Methods: Community service activities are carried aout throught health education with lecture methods, discussions and simulations of how to use PPE (Personal Proctection Equipment) such as masks. Results: The results of community service activities carried out have a positive impact and the community responds by implementing it in their daily lives. People ate starting to realize how important it is to use personal proctection during their daily activities which will have an impact on their health and safety during the COVID-19 pandemic. Conclusions: The implementation of community service activities can optimize the use of PPE to prevent COVID-19 transmission to the community and it is hoped that such activities can be carried out continuously so that COVID-19 transmission does not occur in the community.